Risk factors assessment for nasal colonization of Staphylococcus aureus and its methicillin resistant strains among pre-clinical medical students of Nepal. (December 2016) - Ansari, Shamshul; Gautam, Rajendra; Shrestha, Sony; Ansari, Safiur; Subedi, Shankar; Chhetri, Muni
Abstract Background Staphylococcus aureus (S. aureus ), a normal flora of nasal cavity, can cause minor to life threatening invasive diseases and nosocomial infections. Methicillin resistant strains ofS. aureus are causing a great challenge for treatment options. Therefore, the purpose of this study was to assess the nasal carriage rate ofS. aureus, its methicillin resistant strains and risk factors in medical students prior to clinical exposure. Methods The bacterial growth ofS. aureus from nasal swab culture was identified by using standard microbiological methods recommended by American Society for Microbiology. Modified Kirby–Bauer disk diffusion method was used for antibiotic susceptibility testing and methicillin resistance was confirmed using cefoxitin and oxacillin disks. D-zone test method was used to determine the inducible clindamycin resistance. Results Among 200 participants, nasal carriage ofS. aureus was detected from 30 (15 %) subjects. Upper respiratory tract infections significantly (P < 0.05) contributed the carriage ofS. aureus and their methicillin resistant strains. All of the isolates were reported to be susceptible to vancomycin and teicoplanin.S. aureus strains detected from 8 (4 %) students were confirmed to be methicillin resistant. Conclusions The result of our study demands for strict policy to screen all the students for nasal carriage ofS. aureus and its MRSA strains to minimize the transmission of this organism from community to hospital settings.